(untitled) (Anclajes, 2013)
In the novels Fuegia (1991) by Eduardo Belgrano Rawson and La tierra del fuego (1998) by Sylvia Iparraguirre, the indigenous inhabitants and the territory of Tierra del Fuego become representable through gazes and voices that (re)produce ethnical, linguistic and national borders that take root in the Nineteenth century. Following this, two kinds of erasure can be observed. On the one hand, by focalizing on the conflicts between the British and the Fuegians, the colonizing role of the Argentine State towards the territory and its inhabitants is made invisible. On the other hand, through a narration that avoids problematizing the use of the Spanish language for the writing of history, the indigenous people are made invisible as subjects. This allows us to propose that in the Argentinian literature of the end of the Twentieth Century some of the traits of the utopia of a monoglossic nation are still at work.